PEMANFAATAN SUDUT BACA SEBAGAI UPAYA PENGUATAN LITERASI SISWA SEKOLAH DASAR - Syafruddin Muhdar; Ririn Andriani; Rani Kurniawati Rani; Riadhatul Fardhani; Ria Farida; Risa Ardila Sari Sahwan; Rahmatika (STKIP Subang, 2026)
This study aims to examine the utilization of reading corners as an effort to strengthen literacy among elementary school students. Reading literacy is a fundamental skill that plays an important role in supporting students' academic success. However, low reading interest remains a common issue in elementary school environments. Reading corners serve as a simple innovation that can create a literate and enjoyable learning environment. This study employs a qualitative approach using a literature review method to analyze various relevant sources related to the use of reading corners. The results indicate that reading corners can increase students’ interest in reading, enrich vocabulary, and gradually build reading habits. In addition, the presence of an attractive reading corner, supported by the role of teachers and a conducive school environment, is a key factor in its success. Therefore, the utilization of reading corners can be an effective strategy for strengthening literacy among elementary school students.